2003
DOI: 10.1046/j.1469-0691.2003.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

A common clone of erythromycin-resistant Streptococcus pneumoniae in Greece and the UK

Abstract: The present study showed that erythromycin resistance among the S. pneumoniae isolates was mostly owing to the efflux mechanism and suggested a possible clonal spread of serotype 14 erythromycin-resistant S. pneumoniae strains between Greece and the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…In Europe, it is now being increasingly reported from France and Spain. The present study shows that in France (87.5%), Spain (77.3%), Switzerland (80%), and Poland (100%), strains are predominantly erm(B) positive, whereas high levels of mef(A)-positive strains are reported from Greece (100%) and Germany (33.3%), confirming the findings of other investigators (6,7,20,21,25,26). Notably, none of the strains was found to be mef(A)-and erm(B)-negative, suggesting the absence of one of the recently described new macrolide resistance mechanisms, such as mutations in the 23S rRNA or alterations in ribosomal proteins L4 and L22.…”
Section: Discussionsupporting
confidence: 91%
“…In Europe, it is now being increasingly reported from France and Spain. The present study shows that in France (87.5%), Spain (77.3%), Switzerland (80%), and Poland (100%), strains are predominantly erm(B) positive, whereas high levels of mef(A)-positive strains are reported from Greece (100%) and Germany (33.3%), confirming the findings of other investigators (6,7,20,21,25,26). Notably, none of the strains was found to be mef(A)-and erm(B)-negative, suggesting the absence of one of the recently described new macrolide resistance mechanisms, such as mutations in the 23S rRNA or alterations in ribosomal proteins L4 and L22.…”
Section: Discussionsupporting
confidence: 91%
“…The increase in the M phenotype among pneumococci reported in some European countries has been associated with the England 14 -9 clone of serotype 14, which harbors the mefA subclass of the mefA gene (1,5,8,16). In our study, serotype 14 was also the most frequently serotype found, but the Spain 9V -3 clone of serotype 14 with mefE was more prevalent than the England 14 -9 clone with mefA.…”
supporting
confidence: 49%
“…The England 14 -9 clone, first described in the United Kingdom (11), is characterized by the presence of the mefA subclass mefA gene, which is part of a genetic element (Tn1207.1) that has been found in strains from Italy and the United Kingdom (1,5). This clone is an important cause of meningitis throughout the United Kingdom (1,11), and it has been recently described in Italy (16), Greece (8), and now in Spain, suggesting the spread of this clone among Mediterranean countries.…”
mentioning
confidence: 99%
“…Clones England 14 -9 and Taiwan 19F -14 are the major contributors to the worldwide dissemination of M phenotype strains (7, 12; http://www.mlst.net). The England 14 -9 clone harboring mef(A) has been described as being predominant among M phenotype pneumococci isolated in England, Italy, and Greece (1,9). In contrast, the strains of the England 14 -9 clone described in the United States carried the mef(E) gene (12).…”
mentioning
confidence: 99%